Decaimento exponencial para a equação da onda semilinear com dissipação localmente distribuída - Sousa, Jakcney Luan Azevedo de (2014)
We consider the semilinear wave equation utt u+f(u)+a(x)ut = 0 in a bounded domain Q Rn+1, with su ciently regular boundary , subject the boundary condition u = 0. We investigate the existence, uniqueness and asymptotic behavior, when t ! 1, of solution, considering a 2 L1+ ( ) and f under some adequate conditions.